Mutation Testing Approach to Negative Testing - Joanna Strug (Journal of Engineering)
Negative testing deals with an important problem of assessing a system ability to handle unexpected situations. Such situations, if unhandled, may lead to system failures that in some cases can have catastrophic consequences. This paper presents a mutation testing-based approach for generation of test cases supporting negative testing. Application of this approach can provide, in a systematic and human-unbiased way, test cases effectively testing wide range of unexpected situations. Thus, it can contribute to improvement of a tested system. The paper formally defines mutation operators used to control the generation process, describes a generic framework for the generation and execution of the test cases, and explains how to interpret results.